Posterior left pericardiotomy for the prevention of atrial fibrillation after cardiac surgery: an adaptive, single-centre, single-blind, randomised, controlled trial. Issue 10316 (4th December 2021) - Gaudino, Mario; Sanna, Tommaso; Ballman, Karla V; Robinson, N Bryce; Hameed, Irbaz; Audisio, Katia; Rahouma, Mohamed; Di Franco, Antonino; Soletti, Giovanni J; Lau, Christopher; Rong, Lisa Q; Massetti, Massimo; et al.
Summary: Background: Atrial fibrillation is the most common complication after cardiac surgery and is associated with extended in-hospital stay and increased adverse outcomes, including death and stroke. Pericardial effusion is common after cardiac surgery and can trigger atrial fibrillation. We tested the hypothesis that posterior left pericardiotomy, a surgical manoeuvre that drains the pericardial space into the left pleural cavity, might reduce the incidence of atrial fibrillation after cardiac surgery. Methods: In this adaptive, randomised, controlled trial, we recruited adult patients (aged ≥18 years) undergoing elective interventions on the coronary arteries, aortic valve, or ascending aorta, or a combination of these, performed by members of the Department of Cardiothoracic Surgery from Weill Cornell Medicine at the New York Presbyterian Hospital in New York, NY, USA. Patients were eligible if they had no history of atrial fibrillation or other arrhythmias or contraindications to the experimental intervention. Eligible patients were randomly assigned (1:1), stratified by CHA2 DS2 -VASc score and using a mixed-block randomisation approach (block sizes of 4, 6, and 8), to posterior left pericardiotomy or no intervention. Patients and assessors were blinded to treatment assignment. Patients were followed up until 30 days after hospital discharge. The primary outcome was the incidence of atrial fibrillation during postoperative in-hospital stay, which was assessed in the intention-to-treat (ITT) population. Safety was assessed in the as-treated population. This study is registered with ClinicalTrials.gov, NCT02875405, and is now complete. Findings: Between Sept 18, 2017, and Aug 2, 2021, 3601 patients were screened and 420 were included and randomly assigned to the posterior left pericardiotomy group (n=212) or the no intervention group (n=208; ITT population). The median age was 61·0 years (IQR 53·0–70·0), 102 (24%) patients were female, and 318 (76%) were male, with a median CHA2 DS2 -VASc score of 2·0 (IQR 1·0–3·0). The two groups were balanced with respect to clinical and surgical characteristics. No patients were lost to follow-up and data completeness was 100%. Three patients in the posterior left pericardiotomy group did not receive the intervention. In the ITT population, the incidence of postoperative atrial fibrillation was significantly lower in the posterior left pericardiotomy group than in the no intervention group (37 [17%] of 212 vs 66 [32%] of 208 [p=0·0007]; odds ratio adjusted for the stratification variable 0·44 [95% CI 0·27–0·70; p=0·0005]). Two (1%) of 209 patients in the posterior left pericardiotomy group and one (<1%) of 211 in the no intervention group died within 30 days after hospital discharge. The incidence of postoperative pericardial effusion was lower in the posterior left pericardiotomy group than in the no intervention group (26 [12%] of 209 vs 45 [21%] of 211; relative risk 0·58 [95% CI 0·37–0·91]). Postoperative major adverse events occurred in six (3%) patients in the posterior left pericardiotomy group and in four (2%) in the no intervention group. No posterior left pericardiotomy related complications were seen. Interpretation: Posterior left pericardiotomy is highly effective in reducing the incidence of atrial fibrillation after surgery on the coronary arteries, aortic valve, or ascending aorta, or a combination of these without additional risk of postoperative complications. Funding: None